Interaction of human HelQ with DNA polymerase delta halts DNA synthesis and stimulates DNA single-strand annealing. Issue 4 (31st January 2023) - He, Liu; Lever, Rebecca; Cubbon, Andrew; Tehseen, Muhammad; Jenkins, Tabitha; Nottingham, Alice O; Horton, Anya; Betts, Hannah; Fisher, Martin; Hamdan, Samir M; Soultanas, Panos; Bolt, Edward L
Abstract: DNA strand breaks are repaired by DNA synthesis from an exposed DNA end paired with a homologous DNA template. DNA polymerase delta (Pol δ) catalyses DNA synthesis in multiple eukaryotic DNA break repair pathways but triggers genome instability unless its activity is restrained. We show that human HelQ halts DNA synthesis by isolated Pol δ and Pol δ-PCNA-RPA holoenzyme. Using novel HelQ mutant proteins we identify that inhibition of Pol δ is independent of DNA binding, and maps to a 70 amino acid intrinsically disordered region of HelQ. Pol δ and its POLD3 subunit robustly stimulated DNA single-strand annealing by HelQ, and POLD3 and HelQ interact physically via the intrinsically disordered HelQ region. This data, and inability of HelQ to inhibit DNA synthesis by the POLD1 catalytic subunit of Pol δ, reveal a mechanism for limiting DNA synthesis and promoting DNA strand annealing during human DNA break repair, which centres on POLD3.